Tanggung Jawab Negara Terhadap Pencemaran Akibat Industri Pertambangan Pada Wilayah Perbatasan Laut Menurut Hukum Lingkungan Internasional - Eliezer Sasake; Josina Augustina Yvonne Wattimena; Richard Marsilio Waas (TATOHI: Jurnal Ilmu Hukum, 2022)
Introductioan: Environmental pollution in marine areas comes from human activities in using natural resources, one of which is the result of the mining industry, both mining from land and at sea.Purposes of the Research: This writing aims to understand and know the regulation of pollution caused by the mining industry in marine border areas according to international environmental law.Methods of the Research: The research method in this paper uses a prescriptive analytical research type. The research approach used is a statutory approach, a conceptual approach and a case approach. The procedure for collecting legal materials uses primary legal materials and secondary legal materials through books, articles, journals and the writings of legal experts, as well as legal materials analysis techniques in this study using qualitative analysis techniques.Results of the Research: The results of this study indicate that the regulation on the protection and responsibility of the state against marine pollution has been explicitly regulated in The United Nations Convention on the Law of the Sea (UNCLOS) 1982 and the 1972 Stolckhom Declaration on the Environment. The form of responsibility contained in a case of cross-border pollution is absolute responsibility (strict liability). International Dispute Resolution can be carried out in many ways as long as these methods do not conflict with the United Nations Charter, namely peaceful means. Every violation of international law for which there is no reason to erase the fault, so that it can be held accountable